Everyday cognitive failure and depressive symptoms predict fatigue in sarcoidosis: A prospective follow-up study. (May 2018) - Hendriks, Celine; Drent, Marjolein; De Kleijn, Willemien; Elfferich, Marjon; Wijnen, Petal; De Vries, Jolanda
Abstract: Background: Fatigue is a major and disabling problem in sarcoidosis. Knowledge concerning correlates of the development of fatigue and possible interrelationships is lacking. Objective: A conceptual model of fatigue was developed and tested. Methods: Sarcoidosis outpatients ( n  = 292) of Maastricht University Medical Center completed questionnaires regarding trait anxiety, depressive symptoms, cognitive failure, dyspnea, social support, and small fiber neuropathy (SFN) at baseline. Fatigue was assessed at 6 and 12 months. Sex, age, and time since diagnosis were taken from medical records. Pathways were estimated by means of path analyses in AMOS. Results: Everyday cognitive failure, depressive symptoms, symptoms suggestive of SFN, and dyspnea were positive predictors of fatigue. Fit indices of the model were good. Conclusions: The model validly explains variation in fatigue. Everyday cognitive failure and depressive symptoms were the most important predictors of fatigue. In addition to physical functioning, cognitive and psychological aspects should be included in the management of sarcoidosis patients. Highlights: Fatigue is a major and disabling problem in sarcoidosis. It is important to examine the potential persisting factors of fatigue in sarcoidosis. Everyday cognitive failure, depressive and SFN suggestive symptoms are predictors of fatigue. Cognitive and psychological aspects should be an integral part of the management of sarcoidosis. Multidisciplinary management is mandatory in sarcoidosis patients.